Analysis of asymmetry of bilateral traits of pholidosis of racerunner Eremias arguta (Pallas, 1773) (Sauria, Lacertidae) (Experimental biology, 2015)
Full statistical analysis of fluctuating asymmetry of 8 bilateral traits of pholidosis of racerunner Eremias arguta (Pallas, 1773) was conducted from the southern foothills of Zhetysuskij Alatau (south-east of Kazakhstan, Konyrolen depression). Directional asymmetry is absent, and shown by the type of asymmetry is fluctuating. The exception was the characters of «the number of scales to bend the kneeә (significantly higher in females on the left than on the right (Р≤0,05)). Two traits were size dependent at females and they are excluded from the list of characteristics that can be used for further analysis. Demonstrated the absence of sexual differences fluctuating asymmetry of bilateral traits. This will in the future use of the pooled sample of males and females. Was to define a set of representative features for subsequent analysis of the populations of colored barbs in Kazakhstan.
Keywords: Eremias arguta folidosis; fluctuating asymmetry